Abandonment of Women’s Rights in Child Marriage; An Islamic Law Perspective - Qodariah Barkah; Arne Huzaimah; Siti Rochmiyatun; Andriyani; Zulmi Ramdani (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
The number of child marriages has recently increased significantly, particularly during the Covid-19 pandemic. This is caused by assumption that child marriage will save the child's financial and social security. In fact, child marriage actually causes many problems, especially regarding the abandonment of women's rights in domestic life. This is contrary to the purpose of marriage in Islam which is to create harmonious, prosperous and happy household. This study aims to gain an in-depth understanding on the forms of abandonment of women's rights in child marriage cases and how the Islamic family law perspective percieves it. The data were obtained through observation, interviews, and literature searches. The research location was conducted in Palembang City, South Sumatra, Indonesia. Data analysis is carried out with an interpretive approach to give meaning so that it has coherence between one another. The research findings show that the forms of abandonment of women's rights in child marriage cases include three types, namely the abandonment of economic rights, human rights and reproductive rights. The abandonment occurs because of community’s legal culture which considers the action as commonplace in the household. Even, the victim of abandonment allowed herself stuck in that position. According to Islamic family law, the abandonment of women's rights in the household is an act of disobedience against justice as well husband’s reluctance to the wife. It is a form of violation of the commands of Allah and His Messenger which is is also emphasized in the legislation with the existence of both social and criminal sanctions.